A usability based approach to designing continuous user biometric authentication system - Mugambi Kaburu, Dennis; Sansa‑Otim, Julianne; Mayanja, Kajumba; Mirembe, Drake Patrick; Bulega, Tony (Quality and User Experience, 2018)
Abstract The advent of the internet and associated technologies have revolutionized the way we live and work. Today, organizations both public and private rely heavily on information systems to deliver services. The quality and reliability of services delivered by these systems depends on controlled access to these information systems. In mission, critical systems like online examination and military intelligence, there is need to verify constantly the identity of the user throughout the session of interaction (referred to as “continuous user authentication”). Accordingly, researchers have proposed a number of approaches to address the issues of continuous user authentication. However, these approaches require user collaboration, which affects user performance on the core tasks in the business processes because of user task interruptions. Thus, the approaches have usability challenges. Continuous user Biometric Authentication systems have a usability score of the range 55–60% on a System Usability Scale (SUS) on average, interpreted in SUS score as poor. Therefore, this paper discusses the design of a non-intrusive continuous user biometric authentication approach, which aims at guiding the design of continuous user biometric authentication systems with SUS score above the range of 65% in relation to the context of the primary task in the business process. The cognitive approach proposed incorporates usability quality attribute in respect to the users’ primary tasks on the system by applying results from cognitive psychology. The approach allows a designer to understand the impact of a particular re-authentication method to user performance and satisfaction in a continuous user authentication environment.
Keywords: Usable-security; Continuous user authentication; Biometrics; System Usability Score (SUS)